(untitled) (Fiep Bulletin - online, 2014)
The spinal cord injury reduces the autonomy, predisposing the individual to sedentary lifestyle and consequently the development of the metabolic syndrome. The perivisceral obesity, glucose intolerance, insulin resistance, low HDL-C, high TG levels and hypertension are risk factors for the disease. The aim of the study was to evaluate the influence of strength training on the risk factors of metabolic syndrome in patients with spinal cord injury. There were 20 males , patients with SCI below T7 (low paraplegia), divided into two groups: (G1) group with 8 participants (body mass, 75.58 ± 5.11 kg; % MG, 20.40 ± 6.99) and (G2) control group with 12 members (Body mass, 77.28 ± 8.66 kg; % MG , 23.45 ± 2.83). After the twelve weeks intervention (3x/week, 2-3series, 8-15 repetitions). G1 showed a decrease in abdominal circumference (AC, 105.45 ± 9.09 cm vs 102.16 ± 8.70 cm). Body Mass (75.58 kg ± 5.11 vs 73.40 ± 4.98 kg) and % BF ( 20.40 ± 6.99 vs 18.62 ± 6.17 kg kg) at p <0.05 while there were no alterations in G2. The fat-free mass increased in G1 (28.48 ± 29.55 vs 433 kg ± 4.36 kg, p=0. 000). Decreased systolic blood pressure (138.02 ± 10.24 mmHg vs 136.88 ± 8.46 mmHg). There was improvement of cholesterol serum total (228.63 ± 27.84 mg / dl vs. 208.13 ± 3.02 mg/dl, for p = 0.037), triglycerides (201.5 ± 5.40 mg/dl vs. 172.13 ± 12.55 mg/dl, for p = 0.000), HDL (42.75 ± 6.82 mg/dl vs 49.00 ± 5.45 mg/dl, for p=0.000), LDL (156.76 ± 3,63mg/dl vs 144.45 ± 19.78 mg/dl. G2 no changes. Findings of this study align the evidence described in the Literature about the importance of higher strength levels for the prevention and control of factors syndrome risk. Results also suggest that strength training seems to be an important ally in fighting the disease, especially for injured individuals because it is a form of training perfectly suited to individual physical condition, respecting the limitations imposed by trauma.